Dermoscopy as a prognostic tool for the therapeutic response of phototherapy and methotrexate in psoriasis - Shaimaa I Omar; Eman M Hassan (Wolters Kluwer Medknow Publications, 2020)
Background Methotrexate and phototherapy are traditional treatments for psoriasis, but their prolonged use is associated with cumulative toxicity, so physicians are in a continuous need for tools to predict and monitor the progress of the disease. Objective To detect if there is any role for dermoscopy in determining the psoriatic patients' response to phototherapy and methotrexate. Patients and methods A total of 70 patients with psoriasis were treated by methotrexate or phototherapy with narrow-band ultraviolet B for four months according to their local and general conditions. Psoriasis Area and Severity Index score calculation and dermoscopic examination were done at baseline, after 1 month, and after 4 months of starting treatment. Results A significant association was noted between changes in the vessel distribution in psoriatic lesions and the response to treatment according to Psoriasis Area and Severity Index score assessment along treatment visits, whereas presence of hemorrhagic dots was significantly associated with poor clinical response. Conclusion The use of dermoscopy in assessing vascular distribution and hemorrhagic dots may reflect the severity of psoriasis and can predict the clinical response to either methotrexate or phototherapy.